"The Reflection of the Concept “Goodness” - Allamuratov Aydos Maxsetbaevich (International Journal on Orange Technologies, 2022)
The article provides a linguocultural analysis of the concept and its study, the reflection of the concept goodness in proverbs, which are the spiritual and cultural heritage of the people.